A strong summer intrusion of the Kuroshio and residence time in the northern South China Sea revealed by radium isotopes. (September 2021) - Wang, Guizhi; Sun, Shengyao; Tan, Ehui; Chen, Liwen; Wang, Lifang; Huang, Tao; Zhou, Kuanbo; Chen, Weifang; Guo, Xianghui
Graphical abstract: Highlights: Surface 226 Ra & 228 Ra were presented across the Luzon Strait & in the northern SCS. The Kuroshio water in the surface northern SCS was 23 ± 11%, estimated using 226 Ra. A strong summer intrusion of the Kuroshio occurred extending as far west as 115° E. The residence time of the surface water in the slope and basin was 2.92 ± 2.20 years. Abstract: The Kuroshio intrusion through the Luzon Strait into the northern South China Sea (SCS) is an important contributor to the heat and salt budgets of the SCS and is usually the strongest in winter. The extent of the intrusion in summer and the residence time of the very surface layer (0–5 m) in the northern SCS slope and basin areas, however, are seldom quantitatively evaluated. In this study we investigated surface distributions of radium isotopes ( 226 Ra and 228 Ra) across the Luzon Strait into the northern SCS in late spring to mid-summer to reveal the fraction of the Kuroshio water and the transport path of the Kuroshio intrusion in the northern SCS. The activity of 228 Ra ranged from 0.67 to 23.5 dpm 100 L -1, with the maximum occurring at the lowest salinity of 28.8 on the northern SCS shelf and the minimum appearing east of the Luzon Strait characteristic of the more saline Ra-depleted Kuroshio water. The activity of 226 Ra showed a similar pattern in a smaller range of 4.63–9.64 dpm 100 L -1 . Distributions of 226 Ra and 228 Ra, combined with the distribution of salinity, demonstrate that three water masses contribute to the surface seawater in the northern SCS, the Kuroshio surface water, the plume water, and the island-influenced surface water. We quantified the fraction of the Kuroshio water in the northern SCS, considering the conservation of 226 Ra and salinity, to be in the range of 4 ± 7%–51 ± 4% with an average of 23 ± 11%. The fraction decreased southward and westward from the northwest off the Luzon Strait. The intrusion of the Kuroshio reached as far west as 115° E and as far south as 14° N. The residence time of the very surface water in the northern SCS slope and basin areas was estimated using 228 Ra as a timer to be 0.22 ± 0.59–9.98 ± 0.54 years with an average of 2.92 ± 2.20 years.